Can Mitochondrial DNA be CRISPRized: Pro and Contra. Issue 12 (5th September 2018) - Loutre, Romuald; Heckel, Anne‐Marie; Smirnova, Anna; Entelis, Nina; Tarassov, Ivan
Abstract: Mitochondria represent a chimera of macromolecules encoded either in the organellar genome, mtDNA, or in the nuclear one. If the pathway of protein targeting to different sub‐compartments of mitochondria was relatively well studied, import of small noncoding RNAs into mammalian mitochondria still awaits mechanistic explanations and its functional issues are often not understood thus raising polemics. At the same time, RNA mitochondrial import pathway has an obvious attractiveness as it appears as a unique natural mechanism permitting to address nucleic acids into the organelles. Deciphering the function(s) of imported RNAs inside the mitochondria is extremely complicated due to their relatively low abundance, which suggests their regulatory role. We previously demonstrated that mitochondrial targeting of small noncoding RNAs able to specifically anneal with the mutant mitochondrial DNA led to a decrease of the mtDNA heteroplasmy level by inhibiting mutant mtDNA replication. We then demonstrated that increasing level of expression of such antireplicative recombinant RNAs increases significantly the antireplicative effect. In this report, we present a new data investigating the possibility to establish a CRISPR‐Cas9 system targeting mtDNA exploiting of the pathway of RNA import into mitochondria. Mitochondrially addressed Cas9 versions and a set of mitochondrially targeted guide RNAs were tested in vitro and in vivo and their effect on mtDNA copy number was demonstrated. So far, the system appeared as more complicated for use than previously found for nuclear DNA, because only application of a pair of guide RNAs produced the effect of mtDNA depletion. We discuss, in a critical way, these results and put them in a broader context of polemics concerning the possibilities of manipulation of mtDNA in mammalians. The findings described here prove the potential of the RNA import pathway as a tool for studying mtDNA and for future therapy of mitochondrial disorders. © The Authors. IUBMB Life published by Wiley Periodicals, Inc. on behalf of International Union of Biochemistry and Molecular Biology, 70(12):1233–1239, 2018